Team psychology in sports theory and practice - Cotterill, Stewart (Routledge, 2013)
The ability to mould a group of talented individual athletes into an effective team takes effort and skill. Team Psychology in Sports examines the crucial factors in the development of an effective team, introducing important psychological and organizational concepts and offering evidence-based interventions for enhancing the performance of any sports team. The book neatly bridges the gap between theory and practice, with real sporting case studies, examples and practical tools included in each chapter.